GENDER WAYANG DALAM MESANGIH - I Ketut Yasa (Gelar : Jurnal Seni Budaya, 2012)
Gender wayangÂ is one of Balinese gamelan instruments made of bronze which has ten keys and five notesÂ inÂ slendro tuning. So there is a bass system.Â MesangihÂ is a ceremony for cutting teeth which aims to â€œkillâ€Â sad ripuÂ (six enemies existing in human being) in order that it can be controlled. The ceremony is also meant to purify somethingÂ letehÂ in order to be able to meet Mother and Father (Hyang Widhi) in the life after death.Â MesangihÂ is accompanied by gender wayang melodies in accordanceÂ  with the character of each melody to support the atmosphere needed.Â Key wordsÂ :Â Gender wayang melodies, mesangih